Publishing activity of the 16th-century Czech printer Oldřík Velenský from Mnichov - Mnogoletnaya, Elena Nikolayevna (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения)
The article examines the publishing activities of the Czech typographer Oldřík Velensky from Mnichov, a humanist, a printer, a writer and a translator. The author analyses the genre repertoire of publications published by Oldřík Velenský from Mnichov, his translation work and humanistic studies.